2022
DOI: 10.3390/ijerph191610222
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Energy Expenditure, Screen Time and Social Support in Spanish Adolescents—Towards an Explanatory Model about Health Risk Factors

Abstract: Youth obesity has been a pandemic for decades. One of its causes is a low level of physical activity. It is necessary to know the specific situation of adolescents and the factors that influence it in order to be able to act accordingly. The first aim of the current study is to create an explanatory model to establish the relationships between light physical activity time, light physical activity energy expenditure, screen time and social support. The second aim is to propose a theoretical model specifying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…During this stage, young people are susceptible to influence as their personalities are still developing and therefore not yet established (Slobodskaya 2021), allowing the acquisition of behaviours that are harmful to their physical and mental health, which can lead to problems in later stages of personal development (Melguizo-Ibáñez et al 2020). In this case, the research carried out by Sanz-Martín et al (2022) concluded that during adolescence there is a decrease in physical exercise times, with these results being greater in females than in males (Gentil-Adarve et al 2019). These low levels of physical activity can lead to the development of various cardiovascular diseases (San Román-Mata et al 2020) and a decrease in life expectancy (González-Valero et al 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…During this stage, young people are susceptible to influence as their personalities are still developing and therefore not yet established (Slobodskaya 2021), allowing the acquisition of behaviours that are harmful to their physical and mental health, which can lead to problems in later stages of personal development (Melguizo-Ibáñez et al 2020). In this case, the research carried out by Sanz-Martín et al (2022) concluded that during adolescence there is a decrease in physical exercise times, with these results being greater in females than in males (Gentil-Adarve et al 2019). These low levels of physical activity can lead to the development of various cardiovascular diseases (San Román-Mata et al 2020) and a decrease in life expectancy (González-Valero et al 2017a).…”
Section: Introductionmentioning
confidence: 99%